1973
DOI: 10.1037/h0034816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of teacher sex and student sex on classroom interaction.

Abstract: The behavior of male and female teachers toward male and female students in 16 junior high classrooms during 10 instructional hours was compared using the Brophy-Good Dyadic Coding System. The data show that male and female teachers behave differently in some ways, although they show similar patterns in their treatment of boys and girls. High-achieving boys, relative to other students, received the most favorable teacher treatment. But low-achieving boys, relative to others students, received the poorest conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
69
2
2

Year Published

1977
1977
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(86 citation statements)
references
References 14 publications
(9 reference statements)
12
69
2
2
Order By: Relevance
“…Boys negatively influenced the learning environment by destroying school materials and by behaving disruptively and inappropriately. Less than 50 years later, Good, Sikes and Brophy (1973) reported the same situation. In their survey of earlier research, they stated that many studies had demonstrated that boys were more aggressive and more difficult to manage than girls.…”
Section: Research Overview On Teachers and Disorderly Boyssupporting
confidence: 52%
See 2 more Smart Citations
“…Boys negatively influenced the learning environment by destroying school materials and by behaving disruptively and inappropriately. Less than 50 years later, Good, Sikes and Brophy (1973) reported the same situation. In their survey of earlier research, they stated that many studies had demonstrated that boys were more aggressive and more difficult to manage than girls.…”
Section: Research Overview On Teachers and Disorderly Boyssupporting
confidence: 52%
“…In essence, some boys are more unruly in textile-sloyd lessons. Even so, the results discussed in this article are likely valid for teachers of wood and metal sloyd as well, as earlier findings by Good, Sikes and Brophy (1973) emphasised that even if male and female teachers teach differently, they do not treat male and female pupils differently. Furthermore, Swedish teacher education is similar in all sloyd-subjects when it comes to classroom management training, and the forms of employment are similar: there is usually only one or very few sloyd teachers in each school unit.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Male students may believe mathematics is more a male domain (Olszewski-Kubilius & Wohl, 1993) and therefore females are less able to participate in advanced work in the area. The classroom environment, therefore, has been found to encourage males and to discourage females from achieving excellence in mathematics (Becker, 1981;Good, Sikes & Brophy, 1973;Hart, 1989;Karp & Yoels, 1976;Orenstein, 1994;Sacker, Sacker & Long, 1989;Tobin & Gallagher, 1987). Urging students, particularly females, to take a stab at a problem by welcoming educated guesses, or by encouraging students to work together in small groups composed of more than one girl in each group, may assist in increasing females' confidence in their mathematical prowess (Lockheed & Harris, 1984;Treisman, 1985).…”
Section: Increasing Female Participationmentioning
confidence: 99%
“…Ces résultats qui, toutefois, ne concernent pas la totalité des enseignants, vont dans le sens des études de Basow (1980), Guttentag et Bray (1977), Good, Sikes et Brophy (1973), Etaugh, Collins et Gerson (1975), Serbin étal (1973, Simmons (1980).…”
Section: Vauto-perception (Questions 15 Et 16 De L'annexe)unclassified